Effects of Social Media on Social Relationships: A Descriptive Study on the Impact of Mobile Phones among Youth Population - Rajeev M.M. and Jobilal (International Research Journal of Social Sciences, 2015)
Society is influenced by social media in myriad ways. It is the media that help them to get information to form opinions and make judgments regarding various issues. It is the media which keeps the people updated and informed about what is happening around them and the world. Here the researcher studied the various impacts of mobile phone among the youth in social relationships. The very specific objectives of the study are (1) to study the influence of other social networking sites or contributing factors on the usage of mobile phones among the respondents (2) to study the extent use of that mobile phones are used the respondents (3) to analyze the positive and negative impacts of mobile phones among the respondents. The study uses the simple random sampling method. The samples were collected from the boys and girls of selected classes. The sample size of the study is 50 respondents. The finding and recommendations of the study highlights the vast scope of social media in the development aspects, meanwhile, the negative impact of mobile phones and other associated supplies are very high. The sensitization and intervention programmes are the real need of the hour to control the ill effects of social net working sites among the teenagers.